Training on Making Briquettes from Rice Husk Waste as an Alternative Fuel - Helda Rahmawati; Siti Shalihah; Sari Indriyani; Meyninda Destiara; Khairiatul Muna (Journal of Social Work and Science Education, 2022)
The large number of farmers harvesting rice in peat areas, especially in Malintang village, creates mountains or piles of rice husks along the road. Because the peat area is an agricultural area, there is a lot of rice husk waste. Based on the initial observation of the facilitator team to the community in Malintang village, most people use this rice husk waste for gardening purposes such as being used as a mixture of fertilizer or animal feed. However, this rice husk waste has not been optimally utilized as an alternative fuel. Therefore, the facilitator team wants to facilitate training in making this briquette into one of the alternative energies that can be used by peat communities, especially in Malintang sub-district. This training aims to (1) provide education to the people of Gambut District about the benefits of briquettes as an alternative fuel, (2) provide training to the community on how to make briquettes as an alternative fuel, (3) find out the perception of the peat community regarding briquettes as an alternative fuel. Based on the results of the questionnaire analysis, it was found that 75% of the public's perception of briquette making was that they did not know about how to make briquettes and how to use them, however after training the community had received education about the use of rice husk waste into briquettes.